Ekspansi Pasar Batik Jembatan Akar Melalui Optimalisasi Produksi dan Pemasaran Digital - Adila Adisti; Chairunnisya; Musbatiq Srivani (Program Studi Ekonomi Pembangunan, 2025)
Batik Jembatan Akar is one of the MSMEs located in West Sumatra and is known for its batik products, which display unique motifs typical of Minangkabau culture. This community service activity aims to improve production quality by applying technology, broadening the insights and skills of partners in batik using natural dyes, and strengthening marketing strategies through growth hacking innovation by utilizing digital marketing, sustainable and environmentally friendly packaging. The methods used in this activity are socialization, application of technology, and mentoring and evaluation. The results of this activity show an increase in batik production every month from 10 pieces to 30 batik cloths and the products produced have consistent quality. In terms of marketing, the viewer reach has reached 436 views in each post. Through this community service, the team helps partners expand market share by producing good product standards and using environmentally friendly packaging and marketing through Instagram Ads to reach consumers according to the market share of Jembatan Akar batik.